Reformasi reloaded? Implications of Indonesia's 2014 elections - Felix Heiduk (Stiftung Wissenschaft und Politik (SWP), 2014)
For the third time since the end of the authoritarian Suharto regime the Indonesian people have directly elected their president. The victory of Joko Widodo ("Jokowi"), a self-made businessman from modest upbringings, has spurred hopes for a renewal of Indonesia's reform (reformasi) process, which had for the most part lain dormant during the second term of his predecessor Susilo Bambang Yudhoyono ("SBY"). While the new government has raised high expectations for swift reforms amongst its supporters, it faces a range of imminent challenges. An ailing state budget, bureaucratic red tape, dated infrastructure, as well as reforms in the fields of health care and education are but some of the policy fields that warrant quick action. The first reality check for Jokowi's reform policies will be in parliament, where his coalition currently holds a mere 38 percent of the seats. With regard to Jokowi's strong focus on domestic affairs and his lack of experience in foreign affairs, it is also to be expected that Indonesia will play a less active role in the region in the next couple of years. (SWP-Comments)
Keywords: 320